Suspecting classical homocystinuria in an adolescent born before the newborn screening program - Carvalho, Fábia (2021)
Introduction: Classical homocystinuria (HCU) is an autosomal recessive disorder caused by a deficiency in the cystathionine beta-synthase enzyme and associated with a high probability of vascular complications. Herein is presented the case of an adolescent diagnosed with HCU during cerebral venous sinus thrombosis (CVST) study. Case Report: A 14-year-old girl presented with thrombophilia screening tests suggestive of HCU during CVST study. After referral to an Inherited Metabolic Diseases Unit, she started supplementation with pyridoxine, folic acid, vitamin B12, betaine anhydrous, and cysteine and was advised to restrict natural proteins and methionine from diet. Genetic analysis revealed a homozygous CBS mutation (c.572C>T (p.T191M) with c.699C>T (p.Y233Y) polymorphism. Discussion: In adolescents born before 2004 (year of implementation of the Portuguese newborn screening program), HCU should be considered when studying hypercoagulability syndromes, as it is a treatable condition and treatment can prevent major morbidity and mortality causes.